Authentic Assessment in Higher Education to Increase Critical Thinking and Develop Metacognitive Awareness - Muhammad Ilham Ali; Noldy - Pelenkahu; Herlina - Usman; Olga Anneke Rorintulus (Universitas Syiah Kuala, 2025)
This study highlights the effectiveness of authentic assessment in evaluating higher-order cognitive competencies, including problem-solving, reasoning, analytical thinking, creativity, and the development of metacognitive awareness. Through authentic assessment, students can apply their knowledge and skills in real-world contexts by constructing responses based on critical analysis, identifying cause-and-effect relationships with supporting evidence, and solving problems through logical reasoning. The research employed a descriptive qualitative analysis method, utilizing tests, surveys, and document analysis as instruments. The study involved 40 fifth-semester students from the English Education Department enrolled in an Advanced Writing course. Authentic assessment was implemented in the context of expository writing, specifically problem-solution essays, with a focus on (1) formulating relevant and critical issues and arguments, (2) establishing clear and logical connections between ideas, and (3) presenting multiple solutions supported by sound reasoning. The findings indicate that students' average performance in writing expository texts reached a score of 78, classified as high or good. Given its advantages, authentic assessment is strongly recommended in teaching and learning. It offers several benefits, including (a) promoting students creative and critical thinking abilities, (b) enabling them to construct meaningful learning experiences by selecting and organizing relevant responses through situational analysis, and (c) integrating instructional, learning, and assessment activities. Furthermore, for students, authentic assessment significantly enhances academic writing proficiency and productivity, equipping them with essential skills for handling more complex tasks in real-world contexts.